2020
DOI: 10.3390/pharmaceutics12010062
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies for the Treatment of Brain Metastases, a Dream or a Reality?

Abstract: The incidence of brain metastases (BM) in cancer patients is increasing. After diagnosis, overall survival (OS) is poor, elicited by the lack of an effective treatment. Monoclonal antibody (mAb)-based therapy has achieved remarkable success in treating both hematologic and non-central-nervous system (CNS) tumors due to their inherent targeting specificity. However, the use of mAbs in the treatment of CNS tumors is restricted by the blood–brain barrier (BBB) that hinders the delivery of either small-molecules d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 124 publications
(138 reference statements)
1
20
0
Order By: Relevance
“…This process entails binding of the ligand to the receptor, internalization of the ligand–receptor complex, and exocytosis on the abluminal side of the cell [ 3 ]. It is important to keep in mind, however, that high-affinity antibodies toward receptors that mediate RMT will follow the lysosomal pathway when internalized, which results in their degradation [ 22 ]. While this phenomenon creates a challenge in using the RMT mechanism, optimizing the affinity of the ligand that is targeting these receptors has proved to be an effective strategy [ 22 ].…”
Section: Delivery Of Antibodies Into the Brain: Mechanism Of Deliverymentioning
confidence: 99%
“…This process entails binding of the ligand to the receptor, internalization of the ligand–receptor complex, and exocytosis on the abluminal side of the cell [ 3 ]. It is important to keep in mind, however, that high-affinity antibodies toward receptors that mediate RMT will follow the lysosomal pathway when internalized, which results in their degradation [ 22 ]. While this phenomenon creates a challenge in using the RMT mechanism, optimizing the affinity of the ligand that is targeting these receptors has proved to be an effective strategy [ 22 ].…”
Section: Delivery Of Antibodies Into the Brain: Mechanism Of Deliverymentioning
confidence: 99%
“…The high demand for mAbs is well-founded, and despite the challenges associated with industrial grade production of homogeneous and efficacious product, they have been used in a number of novel applications [22,23]. Research has suggested mAbs, when combined with BBB peptide shuttles, could penetrate the BBB, and deliver an effective treatment for brain metastases [9]. This could occur through the use of antibody fragments to reduce molecular weight, or the incorporation of cell penetrating peptides (CPPs) into mAbs to deliver large cargoes across cell membranes, and even the BBB [24].…”
Section: Biopharmaceuticalsmentioning
confidence: 99%
“…oral, pulmonary, transdermal), and variation in pharmacokinetic parameters, such as half-life (t 1/2 ), protein binding, and bioavailability. Their comparatively large size means it is unusual for biopharmaceuticals, even small antibody fragments, to cross the blood brain barrier (BBB) [9]. Although this can limit their application to brain disorders, it also means there is reduced risk of unwanted side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The brain is a common sanctuary site for SCLC metastases, and patients with CNS metastases typically have a poor prognosis [63]. The blood‐brain barrier limits the delivery of chemotherapy and ICIs to CNS disease, although T cells can more effectively cross, highlighting a potential role for ICIs in CNS metastases [64–66]. As accrual was limited to ECOG PS ≤1 patients and those with treated and or stable/asymptomatic CNS disease, relatively few patients with CNS metastases were accrued to IMpower 133 [37], CASPIAN [40], or KEYNOTE‐604 [48] (8.5%─14.5%, Table 4) compared with actual clinical practice (15%–20%) [67].…”
Section: Discussionmentioning
confidence: 99%